Orientasi Pendidikan: Dari Modernisme ke Postmodernisme - Sultoni, Agus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2020)
Modernism has become the pinnacle of a career from rationality that has made spectacular changes in various fields of life. But on the other hand, modernism must lose the foundation of religious spirituality, in which modern humans are increasingly losing their human status and identity. Postmodernism realizes that the modern dimension that emphasizes empirical and rational considerations is not sufficiently able to answer the existing dynamic problems of education. This paper examines education in an effort to deconstruct the philosophical foundation of modernism, to then consider the presence of postmodernism as part of a solution. Although for many, postmodernism is still seen as just a superficial and empty intellectual mode, reactionist reflection. However, on the diametric side, postmodernism is able to attract the attention of the wider community to leave the world of academia. Many of the educational practices unconsciously reflect the spirit of postmodernism, so it is worth fighting for.